2008
DOI: 10.1111/j.1740-0929.2007.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in estrogen receptor alpha expression in the bursa of Fabricius during chick embryonic development

Abstract: Sex steroid hormones have been reported to be modulators that augment or suppress immune functions. Applying estrogen to chick embryos has been reported to influence antibody production after hatching, suggesting that estrogen acts on B cell differentiation and proliferation in the bursa of chick embryos. We previously reported the presence of estrogen receptor a (ERa) in the bursa during the late period of embryogenesis. In the present study we examined the time course of ERa expression in the bursa of chick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…7,8) In present study, we also found that ER mRNA was expressed in the chick thymus and BF by RT-PCR analysis. In this study, ER expression was established by two methods, immunohistochemistry and RT-PCR analysis, in the chick thymus and the BF.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…7,8) In present study, we also found that ER mRNA was expressed in the chick thymus and BF by RT-PCR analysis. In this study, ER expression was established by two methods, immunohistochemistry and RT-PCR analysis, in the chick thymus and the BF.…”
Section: Discussionmentioning
confidence: 48%
“…Shin et al reported that the lymphoid follicle, the stromal area, and the surface epithelial areas expressed ER, but that the lymphocytes showed negative results for ER expression. 8) These discrepancies might be explained by differences in the methods used for tissue fixation. In previous studies, the formalin fixation method and paraffin-embedded sections were used; 7,8) in contrast, in the study, frozen sections were used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations